2021
DOI: 10.1186/s12893-021-01072-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for small bowel obstruction after open rectal cancer resection

Abstract: Background Small bowel obstruction (SBO) is observed in around 10% of patients with prior open abdominal surgery. Rectal resection causes the highest readmission rates. The aim of this study was to investigate risk factors for readmission for SBO and causes for SBO in patients who needed surgery following rectal cancer surgery. Methods A population-based registry with prospectively gathered data on 752 consecutive patients with rectal cancer who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Nevertheless, our estimates of relative SBO incidence after both colon and rectal cancer surgery were similar to those reported by others [4,12]; also SBO surgery was as common as in other studies [12,41]. After rectal cancer surgery, slightly fewer patients experienced SBO and SBO surgery than reported in many studies [6,18,42].…”
Section: Radiotherapysupporting
confidence: 90%
See 4 more Smart Citations
“…Nevertheless, our estimates of relative SBO incidence after both colon and rectal cancer surgery were similar to those reported by others [4,12]; also SBO surgery was as common as in other studies [12,41]. After rectal cancer surgery, slightly fewer patients experienced SBO and SBO surgery than reported in many studies [6,18,42].…”
Section: Radiotherapysupporting
confidence: 90%
“…In line with previous studies, SBO surgery was twice as common after open surgery compared with after MIS. Conservatively managed SBO in rectal cancer patients is reported to occur in 5%-18% of non-irradiated patients [16,45] compared with 12%-29% after radiotherapy [16,18]. In this aspect, our study displayed a cumulative incidence similar to that reported in other studies [15][16][17][18]; however, a small study with 15-year follow-up found a much higher cumulative incidence (29%) [45].…”
Section: Radiotherapysupporting
confidence: 83%
See 3 more Smart Citations